Sistem Penyeleksi Penerima Bantuan Beras Miskin Kauman Kidul Menggunakan Metode Weighted Product Berbasis Mobile - Christine Dewi; Yeremia Yulianto (Maranatha University Press, 2018)
The problem of poverty is one of the problems that has not been resolved yet in almost all developing countries such as Indonesia. The problem of poverty also affects the health education and income. The government has conducted various means to overcome the problem of poverty but it still has not been decreased yet because of a lot of errors in the distribution of assistance. Decision support system (DSS) is one of the methods to resolve the problem of poverty and errors in the distribution of assistance. Weighted Product methods (WP) is included of category of DSS which very suitable to select many of criteria that have provided by the government. WP method also gives results that are calculated very accurately and can be called as a method of ranking. This system becomes the solution and makes the distribution of assistance easier for administrative village officers. The system is used to select acceptance to help poor rice-based mobile. Using Weighted Product method, this system can run well proved by the valid result of comparison of Excel calculation with the calculation of existing algorithms in the system.